Press release from Joint Press and Publicity Department, Trades Union Congress and Labour Party, 26 February 1926, re: The Mining Crisis (page 1)
1926-02-26 "Press release from Joint Press and Publicity Department, Trades Union Congress and Labour Party, 26 February 1926, re: The Mining Crisis (page 1)" [g0695001.jpg], 26 February 1926 The Build Up